(untitled) (Cardiovascular Journal, 2014)
Background: About one-third of all elective PCI procedures are associated with significant myocardial injury termed peri-procedural myocardial injury (PMI), which has been associated with increased subsequent mortality. The stent length is one of the factors that can predict procedure related Troponon I release. Methods: This interventional study was carried out to evaluate the influence of stent length on peri procedural myocardial injury by measuring post procedural release of Troponin I after percutaneous coronary intervention. Patients with e70% stenosed single vessel disease undergoing percutaneous coronary intervention with single stent were considered. Exclusion criteria were pre-procedural elevation of cardiac Troponin I above the 99th percentile of upper reference, severely ill patients. Total 90 consecutive patients were included. Among them 45 patients had d 20mm long stent (group A) and rest 45 patients had > 20mm long stent (group B). Blood samples for Troponin I were collected before procedure and 12 hours after procedure. Results: Baseline characteristics including age, sex, risk factor for ischaemic heart disease and clinical diagnoses were almost similar between the two groups. During procedure no complications concurred 93.3% patients in group A and 68.9% patients in group B (p<0.05). Post procedural Troponin I level in group A was 0.47 ± 0.54 and in group B was 0.99 ± 1.09 (p<0.05). The stent length and post procedural Troponin I level had moderate correlation (r=0.41) (p<0.05). In hospital complications in two groups include persistent angina (6.7% vs. 11.1%), new ischaemic episode (0.0% vs. 4.4%) (p>0.05). There were no myocardial infarction, acute left ventricular failure, emergency CABG, arrhythmia and death in both groups. Durations of hospital stay were significantly higher in group B then group (4.53 ± 0.63 vs. 4.07 ± 0.65, p<0.05). Conclusion: The incidence of procedural myocardial injury and procedural complications are more in longer stent group. So limiting the stent length by spot-stenting the lesions rather than covering the entire vessel between lesions may reduce peri-procedural release of cTnI and improve post procedural prognosis. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18358 Cardiovasc. j. 2014; 6(2): 143-148